Electrical and Magnetic Properties of Pb0.8La0.2Fe0.1Cr0.1Ti0.8O3. Issue 201 (2nd September 2019) - Nayak, Amrita; Patri, S. K.; Deepti, P. L.; Behera, B.
Abstract: The dielectric spectroscopy of a new ceramic material; Pb0.8 La0.2 Fe0.1 Cr0.1 Ti0.8 O3 has been studied. The compound was prepared by solid-state reaction method. The structural study from X-ray diffraction technique shows the formation of polycrystalline sample with orthorhombic crystal system at room temperature. Dielectric property of this material has been characterized in the temperature range of 25–450°C and frequency range of 100 Hz – 1 MHz respectively. The phase transition temperatures were at two different temperatures for each frequency. The nature of ac conductivity shows the negative temperature coefficient of resistance type behavior of the material.